NutriColoring: designing a doodling toolkit to support daily self-reported dietary assessment among office workers - Pan, Sibo; Ren, Xipei; Vos, Steven; Brombacher, Aarnout (Frontiers in Psychology, 2023)
This study was motivated by a desire to help working-age individuals gain a better understanding of their daily nutritional intakes with a new self-reported dietary assessment method, because an unhealthy eating behavior increases the risks of developing chronic diseases. In this paper, we present the design and evaluation of NutriColoring, a food diary that leverages doodling on sketches to report and reflect on everyday diet in the working context. Through a two-week field study involving 18 participants, the usefulness of NutriColoring in facilitating dietary assessment was tested by making comparisons with the typical bullet diary method. Our quantitative results showed that NutriColoring provided users with improved dietary assessment experience and intrinsic motivations, with significantly low task frustration and high enjoyment. Because of the freedom and playfulness in reporting intakes at work, the interview findings showed high acceptance of employing NutriColoring at work. This paper is concluded with a set of implications for design and development of doodling toolkit to support healthy eating behaviors among office workers.